2023
DOI: 10.5194/acp-23-7569-2023
|View full text |Cite
|
Sign up to set email alerts
|

Arctic observations of hydroperoxymethyl thioformate (HPMTF) – seasonal behavior and relationship to other oxidation products of dimethyl sulfide at the Zeppelin Observatory, Svalbard

Abstract: Abstract. Dimethyl sulfide (DMS), a gas produced by phytoplankton, is the largest source of atmospheric sulfur over marine areas. DMS undergoes oxidation in the atmosphere to form a range of oxidation products, out of which sulfuric acid (SA) is well known for participating in the formation and growth of atmospheric aerosol particles, and the same is also presumed for methanesulfonic acid (MSA). Recently, a new oxidation product of DMS, hydroperoxymethyl thioformate (HPMTF), was discovered and later also measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Despite the similar values for the O:C ratio and numC between BB aerosol and the rest of the year, respectively, the BB aerosol shows less variation for each of these three properties. The higher variation in the rest of the year could reflect the different source contributions to the organic aerosol, such as an increased contribution of marine aerosols, i.e., methanesulfonic acid (CH 4 O 3 S), which has a high O:C ratio and is prevalent in May and June . Moschos et al reported O:C ratios from two years (2017–2018) of offline Arctic filter samples analyzed with an aerosol mass spectrometer (AMS) and positive matrix factorization (PMF) that are overall lower (approximately 0.2 to 0.8), although they also show a large spread during the year, similar to our results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the similar values for the O:C ratio and numC between BB aerosol and the rest of the year, respectively, the BB aerosol shows less variation for each of these three properties. The higher variation in the rest of the year could reflect the different source contributions to the organic aerosol, such as an increased contribution of marine aerosols, i.e., methanesulfonic acid (CH 4 O 3 S), which has a high O:C ratio and is prevalent in May and June . Moschos et al reported O:C ratios from two years (2017–2018) of offline Arctic filter samples analyzed with an aerosol mass spectrometer (AMS) and positive matrix factorization (PMF) that are overall lower (approximately 0.2 to 0.8), although they also show a large spread during the year, similar to our results.…”
Section: Resultsmentioning
confidence: 99%
“…The particle inlet of the FIGAERO–CIMS was connected to the whole air inlet via stainless steel tubing (length: approximately 6 m, 4 LPM sampling flow). For more details on the FIGAERO–CIMS operation see Gramlich et al 36 and Siegel et al 37 …”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation